Numerical simulation inversion of creep laws of composite salt layers based on reaming while drilling - Li, Shiyuan; Li, Chenglong; Chen, Zhaowei; Zhai, Wenbao; Chen, Xuefeng; Cao, Jiawei (Frontiers in Earth Science, 2023)
The composite salt layer of the Kuqa piedmont zone in the Tarim Basin is characterized by deep burial, complex tectonic stress, and interbedding between salt rocks and mudstone. Drilling such salt layers is associated with frequent salt rock creep and inter-salt rock lost circulation, which results in high challenges for safe drilling. Especially, the drilling and completion processes of the salt-gypsum layers of the Kumugeliemu Group are found with frequent downhole accidents and complex issues, such as hole shrinkage, sticking, well kick, and lost circulation, which leads to high difficulties in delivering desirable cementing quality and severely hinders the subsequent safe rapid drilling. Reaming while drilling can effectively enlarge the wellbore diameter, provide extra tolerance for creep shrinkage of salt layers, and ultimately help to shorten drilling time, reduce accidents and complex issues, and improve the lifecycle of wells. In this research, a numerical simulation method was developed to invert the creep laws of composite salt layers, based on reaming while drilling. It is generally believed that the dislocation creep mechanism is dominant in coarse-grained salt rocks, while the pressure solution creep mechanism is dominant in fine-grained salt rocks. Here a well in the Dabei area was taken as an example and the numerical simulation of hole shrinkage at the wellbore scale was performed, based on the actual data before and after reaming and also the theoretical analysis of the two salt rock creep mechanisms and corresponding laws. Furthermore, the inversion results were validated using field data. This research discussed the selection of creep parameters and their variation, in cases of the dominance of the dislocation creep and pressure solution creep mechanisms. This presented method can accurately predict the creep behavior of salt layers and can be used as an effective supplement tool for other test methods like laboratory experiments.